Global distribution and gap analysis of equine housing research: The findings so far and where to go next - Theresa Robertson; Ella Thomas; Gareth Starbuck; Kelly Yarnell (Animal Welfare)
As a free-ranging, social species, the housing of horses (Equus caballus) may limit their opportunity to display natural behaviour, compromising well-being. This review records and presents studies that have investigated horse housing design, evaluates the location and number of studies carried out to date, and reports the methods used to assess impact on equine well-being. A Boolean search was conducted in two databases: Web of Science and Scopus, filtered according to Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) protocol, resulting in 60 peer-reviewed papers for evaluation. Key findings are that a significant amount of work to date has been carried out in Europe and the USA, and the frequency of horse housing studies has steadily increased over the last 33 years, with 52% of them occurring in the last eight years. Health and welfare measures indicate benefits of housing horses in more natural management systems, particularly with conspecifics. Generally, the studies reviewed were only conducted in the short term, therefore future research should aim to increase the length of time over which housing is evaluated, particularly to ensure studies continue beyond an adaptation period. The review also highlights a requirement for more standardised methodology in housing welfare evaluation to allow for more meaningful comparisons to be made. Studies seeking to improve horse welfare in existing housing systems, in the face of limited space or other management constraints, are of high value to the end user and are encouraged. The studies reviewed here represent a significant and diverse body of work from which gaps in knowledge and future research directions can be determined.